A Conception of Teaching - Gage, N. L. (Guildford : Boulder : NetLibrary, Incorporated [Distributor], 2009)
The literature of the behavioural and social sciences is full of theory and research on learning and memory. However, teaching is where learning and memory theory should pay off."A Conception of Teaching" dedicates a chapter to each of the following important components: the need for a theory.
Includes bibliography references and indexes.
Keywords: Teaching; EDUCATION -- Teaching Methods & Materials -- General; Sciences sociales